Visualizing cause-and-effect relationships in utilitarian educational processing in the course of "natural science" - Kalelova, Gulfat; Abdimanapov, Bakhadurkhan; Damenova, Aigul; Demeuov, Arman; Sadirbekova, Dinara (International Journal of Innovative Research and Scientific Studies, 2025)
This paper examines the pedagogical possibilities of using illustrative material to activate students' practice-oriented activities when studying complex relationships in nature. Theoretical analysis has shown that visual illustrative means, including graphs, diagrams, infographics, and interactive models, significantly reduce cognitive load, increase the level of material assimilation, and contribute to a deeper understanding of the processes being studied. For the first time, in this work, a model of receptive illustrative aesthetics (RIE) is postulated. This represents an innovative approach to the use of illustrative material. Within the framework of this model, illustrations cease to be static objects of information transfer and become dynamic means of meaning formation, in which the student acts as an active constructor of knowledge. The main mechanisms of the RIE model include semantic construction, modification of illustrations, and practical interpretation. The theoretical results of the study confirm that the use of RIE in the educational process contributes to the development of critical thinking, analytical skills, and cognitive flexibility of students. Particular attention is given to the prospects for introducing the model into natural science education, as well as to the issues of creating interactive educational platforms and digital tools that support visual modeling of complex processes. This work is a theoretical study based on the analysis of modern pedagogical, cognitive, and multimedia literature. In the future, empirically testing the RIE model and developing methodological recommendations for its implementation in the educational process are proposed.